Optimized Computerized Order Entry can Reduce Errors in Electronic Prescriptions and Associated Pharmacy Calls to Clarify (CTC) - Patel, Jaimin; Ogletree, Richard; Sutterfield, Allison; Pace, John C.; Lahr, Laurene (Applied Clinical Informatics, 2016)
After implementation of a system-wide EMR within our university system, e-prescribing is now commonplace.The authors conducted a study to assess whether optimization of computerized provider order entry (CPOE) can reduce errors in these electronically transmitted prescriptions and would require less frequent interventions from pharmacists, in particular the need for them to “call to clarify” (CTC) details of particular prescriptions. Secondary analysis based on cost assumptions was preformed to presume cost differences before and after optimization changes.In order to generate complete, error-free prescriptions, optimization changes were implemented in the form of in line validation messages. These messages were generated if (1) an order did not specify a provider or pharmacy; (2) the DEA requirements were not met; (3) character limits were exceeded in patient sig or demographics or (4) administration instructions had breaks or had both discrete and free text elements. Retrospectively, prescriptions were randomly selected from a nine month period before and after implementing changes. These prescriptions were analyzed by a pharmacist and a nurse to identify types of errors that would require a CTC to a prescribing provider. Errors were compared statistically to determine effectiveness of changes pre and post optimization.A total of 602 prescriptions were analyzed; 301 before changes and 301 after changes. Of these prescriptions, 20.27% had errors before changes and 12.96% had errors after changes. The decline in the error rate was considered statistically significant for p<0.05. The cost savings were estimated at $76 per 100 prescriptions for pharmacist and physician time-cost estimates combined.Implementing optimization changes to the CPOE resulted in a reduction in error rate requiring pharmacist CTC. This study identifies effective optimization changes for electronic prescribing that can reduce prescribing errors and may result in cost saving.
Keywords: Electronic prescribing; medication errors; CPOE; electronic health records; cost